Patient Preferences for Episodic Migraine Medications: A Discrete Choice Experiment of Self-Injectable Versus Oral Treatments Targeting Calcitonin Gene-Related Peptide Pathway - Whichello C; Viktrup L; Varnado OJ; Quaife M; Trapali M; Tockhorn-Heidenreich A (Patient Preference and Adherence)
Chiara Whichello,1 Lars Viktrup,2 Oralee J Varnado,2 Matthew Quaife,1 Myrto Trapali,1 Antje Tockhorn-Heidenreich3 1Evidera, London, UK; 2Eli Lilly and Company, Indianapolis, IN, USA; 3Eli Lilly and Company, Bracknell, UKCorrespondence: Antje Tockhorn-Heidenreich, Eli Lilly and Company Ltd, 8 Arlington Square West, Downshire Way, Bracknell, RG12 1PU 0044, UK, Tel +44 7901 92 76 75, Email tockhorn_antje@lilly.comPurpose: To understand the trade-offs that patients with episodic migraine are willing to make between attributes of self-injectable calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs) and oral small-molecule calcitonin gene-related peptide receptor antagonists (gepants).Patients and Methods: This was an online discrete choice experiment survey among adults with episodic migraine (≥ 4 and < 15 migraine headache days and < 15 headache days per month over 3 months) in the United States. Hypothetical treatments were characterized by five attributes: chance of ≥ 50% migraine reduction, impact on daily activities, onset of treatment effect, reduction in number of acute medications, and treatment administration. The attributes were selected based on insights gained from a previously conducted literature review and focus group study and aligned with the primary and secondary outcome measures in the double-blind Phase IV head-to-head clinical trial of a CGRP mAb versus gepant.Results: 601 patients (mean age: 44.8 years) completed the survey. Treatment preferences differed significantly between patients. However, for all patients, the most important driver of treatment preferences was the chance of a ≥ 50% reduction in monthly migraine headache days (relative attribute importance: 38.3%), followed by the impact on daily activities (23.5%), the onset of treatment effect (19.5%), the reduction in need for acute medication (15.4%), and finally the route of administration (3.4%). Patients were willing to consider a one-week delayed onset of treatment effect or one-day increased need for acute medication for a higher chance (by 2.06% and 2.65% respectively) of a ≥ 50% reduction in monthly migraine headache days. Patients would trade a reduction of migraine’s impact on daily activities from “extreme” to “moderate” or “minimal” with a lower chance (17.09%, 12.06% respectively) of halving the number of monthly migraine headache days.Conclusion: A ≥ 50% reduction in monthly migraine headache days was the most important treatment attribute for which participants were willing to trade against other attributes. The variation in treatment preferences between patients emphasizes the importance to align decision-making with individual patients’ preferences.Plain Language Summary: Patients seeking care for migraine have varying levels of migraine severity, disability, and different experience with prior treatment. In this study, we researched patients’ preferences for different preventive treatments, by having 601 patients complete an online survey. The survey presented a ‘discrete choice experiment’ where hypothetical migraine treatments described by five treatment characteristics, including whether the treatment was an oral pill or an injection, and asked patients to choose between them. Our results suggested that the chance of reducing the number of migraine days each month by half was the most important therapeutic characteristic, for which patients were willing to exchange other treatment characteristics in order to have a greater chance of achieving this improvement. Patients also valued if treatments worked quickly or reduced the impact of migraine on everyday activities. Whether a treatment was given as an injection or oral pill did not affect preferences.Keywords: gepants, self-injectable treatment, treatment preferences, preventive treatment, United States